Numerical Solution of Three-Dimensional Flow over Angled Backward-Facing Step with Raised Upper Wall - S. Bayraktar (Journal of Applied Fluid Mechanics, 2014)
In the present study, results obtained from three-dimensional incompressible flow over backward-facing step in a rectangular duct using Realizable k- turbulence model are reported. Effects of step inclination angle have been investigated for =30, 45, 90 while upper wall of duct kept parallel to the bottom wall and then rose to =6. Reynolds number based on freestream velocity and step height is examined by varying its magnitude in the range of 15,000-64,000. Simulated results are presented for revealing the general flow features and reattachment lengths after a successful validation of the present work with the experimental data of Driver and Seegmiller (1985). It is found that turbulence kinetic energy increases suddenly after the step for both straight and raised upper walls and reaches its maximum at x/h=5 that consistent with the published literature. The size of reattachment lengths increases with the step inclination angle, i.e., maximum reattachment length occurs at 90 for both straight and raised upper walls. It is seen that raising the upper wall leads to longer reattachment lengths.